Protein interactions, calcium, phosphorylation, and cholesterol modulate CFTR cluster formation on membranes - Yimei Wan; Rhea Hudson; Jordyn Smith; Julie D. Forman-Kay; Jonathon A. Ditlev (Proceedings of the National Academy of Sciences, 2025)
The cystic fibrosis transmembrane conductance regulator (CFTR) is a chloride channel whose dysfunction leads to intracellular accumulation of chloride ions, dehydration of cell surfaces, and subsequent damage to airway and ductal organs. Beyond its function as a chloride channel, interactions between CFTR, epithelium sodium channel, and solute carrier (SLC) transporter family membrane proteins and cytoplasmic proteins, including calmodulin and Na+/H+ exchanger regulatory factor-1 (NHERF-1), coregulate ion homeostasis. CFTR has also been observed to form mesoscale membrane clusters. However, the contributions of multivalent protein and lipid interactions to cluster formation are not well understood. Using a combination of computational modeling and biochemical reconstitution assays, we demonstrate that multivalent interactions with CFTR protein binding partners, calcium, and membrane cholesterol can induce mesoscale CFTR cluster formation on model membranes. Phosphorylation of the intracellular domains of CFTR also promotes mesoscale cluster formation in the absence of calcium, indicating that multiple mechanisms can contribute to CFTR cluster formation. Our findings reveal that coupling of multivalent protein and lipid interactions promotes CFTR cluster formation consistent with membrane-associated biological phase separation.